Accelerating Impact of CGIAR Climate Research for Africa - International Institute of Tropical Agriculture (International Institute of Tropical Agriculture, 2021)
AICCRA-Ghana, led by the International Institute of Tropical Agriculture (IITA), will focus on bridging the gap between the research institutes that produce improved technologies and the development organizations that promote the adoption of improved technologies including digital Climate advisories, for the purpose of enhancing the resilience of the country’s agriculture and food systems in the face of climate change while improving livelihoods of hundreds thousands farmers. AICCRA-Ghana will mutualize existing expertise to strengthen the technical, institutional, and human capacity needed to move CGIAR innovations off the shelf and achieve impacts in the country. The project will specifically launch a “One-health platform for climate-driven pests and diseases”. It is an advanced climate-informed One-health innovation that builds on CGIAR’s track records in this area, framing the nexus of crop, livestock, soil and water health for improved human and ecosystem health, food safety and nutrition, and climate change as a complex public health issue. The project is anchored to CGIAR’s multi-stakeholder platform of the Biorisk Management Facility (BIMAF) hosted by IITA’s station in Benin, West Africa, and includes the following partners: CGIAR Climate Agriculture & Food Security (CCAFS) Research Program, International Water Management Institute (IWMI), Alliance Bioversity-CIAT, World Agroforestry (CIFOR-ICRAF), ICRISAT, Center for Agriculture Biosciences International (CABI), Norwegian Institute of Bioeconomy Research (NIBIO), Crop Research Institute (CSIR/CRI), Ministry of Food and Agriculture (MoFA/PPRSD), Ghana Meteorological Agency, Climate Change & Agriculture Department of the University of Development Studies (CCAD/UDS). AICCRA-Ghana will use the CGIAR’s Scaling Readiness Tool to undertake assessments of CSA options for accelerated uptake of innovations. The National Framework for Climate Services (NFCS) and innovation platforms including private sector, Nourishing Africa network and farmers will be capacitated towards identification, promotion and implementation of suitable CIS and best-bet CSA and One-health innovations. Media and mass-campaign awareness will be launched while developing business models and engaging champion women- and youth-led enterprises. Pilot sites will be identified and training provided to farmers for successful implementation of One-health and CSA technologies.